LITERARY STYLE AND NARRATIVE FRAMEWORK IN ANITA DESAI’S CRY, THE PEACOCK AND VOICES IN THE CITY - Monica (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Anita Desai, a prominent contemporary Indian novelist, masterfully blends psychological depth with poetic prose. Her novels emphasize the complexities of the human mind, often using innovative narrative techniques to explore inner realities rather than societal reflections. Desai’s narrative structure focuses on psychological states through vivid imagery, symbolism, and introspection. Desai employs techniques like stream of consciousness, flashbacks, and free indirect discourse to delve into the protagonists' psyches, revealing their internal struggles. Her poetic use of language crafts a subjective universe, where characters seek self- fulfillment amidst societal constraints. While her focus on psychological intricacy and aesthetic design distinguishes her work, Desai’s narrative innovations remain rooted in the broader literary tradition, reflecting a balance between technical sophistication and emotional resonance. Her novels ultimately depict a poignant interplay between the inner rhythms of the mind and the external world.